"In this class we are so different that I can be myself!" Intercultural dialogue in a first grade upper secondary school in Norway. Issue 2 (3rd April 2017) - Solbue, Vibeke; Helleve, Ingrid; Smith, Kari
ABSTRACT: Focus of this article is immigrant youth and Norwegians-born to immigrant parents in upper secondary school in Norway. The study was conducted in a first year of a general study class in upper secondary school, where 11 of 24 students were immigrants. Previous research on immigrants in school tends to show a picture of a marginalized group in Norwegian schools which is characterized by egalitarianism. The research question of the article is: What can we learn from students' experiences with an inclusive class environment based on a case study? What contributes to their experience of a good class environment? Through observation of the class and interviews with students, we find that diversity is accepted. Pupils show mutual respect for each other and they do not define others based on ethnicity. The way in which school and teachers work with the class is of great importance. An intentional structure is framing the possibilities for intersubjective relations. Through these possibilities the participants create mutual meaning.